EFEKTIVITAS MODEL DL BERBASIS PEMBELAJARAN BERDIFERENSIASI DAN MODEL PBL TERHADAP HASIL BELAJAR - Jazilatul Khofshoh; Muhammad Saifuddin Zuhri; Heni Purwati; Adi Wibawa (JURNAL MathEdu (Mathematic Education Journal), 2023)
This research was motivated by the learning outcomes of students who did not complete the KKM in mathematics and the use of learning models that were not optimal. The purpose of this study was to find out whether there were differences in student learning outcomes using the Discovery Learning (DL) learning model based on differentiated learning strategies with the Problem Based Learning (PBL) learning model. The population in this study were all students of class X SMA Negeri 5 Semarang. The type of research used was quasy experiment with a research design using a post-test only nonequivalent control group design using two groups of students who were given different treatments. In the experimental class group 1 using the Discovery Learning (DL) model based on differentiation learning strategies while in the experimental class group 2 using the Problem Based Learning (PBL) learning model. The sampling technique used cluster sampling. The variables used in this research are independent variables and dependent variables. The variables used are the Discovery Learning (DL) model based on differentiated learning strategies and the Problem Based Learning (PBL) model, while the dependent variable is in the form of students' learning outcomes in mathematics. Data analysis techniques in this study were the normality test, homogeneity test and t test. The results showed that there were differences in student learning outcomes using the Discovery Learning (DL) learning model based on differentiation learning strategies with the Problem Based Learning (PBL) learning model.